Particularitys of diagnostics and surgical treatment of primary benigh heart tumors - R. M. Vitovsky; V. V. Isaenko; O. A. Pishchurin; A. G. Goryachev; D. M. Dyadyun; I. G. Yakovenko (Ukrainian Journal of Cardiovascular Surgery, 2017)
In М. M. Amosov Institute of Cardio-Vascular surgery of the Academy of Medical Sciences of Ukraine for period from 1.01.1969 to 1.01.2017 889 patients with primary heart tumors had surgical treatment. The myxomas of heart (MH) was found in 796 (89,5%), from them in 696 (87,4%) cases – MH of left atrium (LA). The other benign heart tumours were observed in 33 (3,7%) cases, malignant heart tumours – in 60 (6,8%). Hospital mortality was 4,9% (39 cases). In the last 16 years a 433 operation were executed without lethal results.